GOING ELECTRONIC: THE BRYN MAWR CLASSICAL REVIEW - O'Donnell, James (Surfaces)

(untitled) (Les Presses de l’Université de Montréal, 1994)
A discussion of the shift that electronic publishing represents, with particular reference to the history of the Bryn Mawr Classical Review and the effect of its shift to electronic publication.